Art therapy and its effectiveness with children who have experienced trauma - Bian, Weiwei (University of Wisconsin-Superior, 2019)
Art therapy is a highly important part of child trauma treatment, Art therapy is a form of expressive therapy that uses the creative process of making art to improve children’s physical, mental, and emotional well-being. The creative process involved in expressing artistically can help children to resolve issues as well as develop and manage their behaviors and feelings, improve self-esteem and awareness. “Art can provide a window to children’s problem, traumatic memories, development, and worldviews” (Malchiodi, 2012). Its primary purpose is to give children another language with which to experience feelings, ideas, perceptions, and observations about themselves, others and the environment. Art therapy will help child work through the traumatic event, it is a regulated mental health profession, using the creative process to enhance child’s experience in a safe environment, structured by the therapist, helps facilitate that process for the client.
Keywords: Child; Trauma; Well-being